EVOLUTION PÅ ARBEJDET: Indblik i en refleksivt selvforandrende kultur - Salamon, Karen Lisa Goldschmidt (Tidsskriftet Antropologi, 2005)
Workplace organisation and employee identities are increasingly spiritualised, the author argues. Management issues are no longer phrased in materialist terms, but regarded as matters of personal intent and cultural meaning. Ethnographic fieldwork is a highly suitable, albeit complex way of studying the production of meaning under modern capitalist forms of work organisation. In the late 1990s, the author conducted four years of multi-sited ethnographic fieldwork amongst European and North American management consultants and Human Resources Managers. Drawing on this fieldwork, she discusses the contemporary concern with evolution and growth at work. She argues that a sub-culturally nourished, neo-spiritual cosmology of self-development, individual responsibility and change has grown conspicuous in (post)-industrial societies. Under neo-liberal, globalising forms of production and governance, ideals of timed, efficient self-management, self-reflexivity and internalised economic rationalities have conquered the discourse of organisational behaviour. Work is rearticulated as a spiritual quest and a personally profound calling. The values-based trend is a significant factor in this, demanding that work be personally meaningful. The practical enactment and production of this meaningfulness make up very relevant fields for contemporary ethnographic study. However, the author also notes, classic ethnographic notions are challenged in this kind of study. Ideas of the informant as a constant subject-position and the field as a stable place are challenged, when those under study are managers and employees who strive to move ever faster and become ever more evolved, self-altering - and thus always “new”.